Counterparty Risk in the Over-The-Counter Derivatives Market - Singh, Manmohan; Segoviano, Miguel (Washington, D.C. : International Monetary Fund, 2008)
The financial market turmoil of recent months has highlighted the importance of counterparty risk. Here, we discuss counterparty risk that may stem from the OTC derivatives markets and attempt to assess the scope of potential cascade effects. This risk is measured by losses to the financial system that may result via the OTC derivative contracts from the default of one or more banks or primary broker-dealers. We then stress the importance of "netting" within the OTC derivative contracts. Our methodology shows that, even using data from before the worsening of the crisis in late Summer 2008, the potential cascade effects could be very substantial. We summarize our results in the context of the stability of the banking system and provide some policy measures that could be usefully considered by the regulators in their discussions of current issues.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet